Managing adipsic diabetes insipidus following anterior communicating artery aneurysm in a subtropical climate. Issue 7 (1st June 2016) - Nolan, Brendan; Inder, Warrick J.
Key Clinical Message: Diabetes insipidus without perception of thirst, as may follow an anterior communicating artery aneurysm, requires prescription of fluid intake as well as desmopressin. The management goal of maintaining a normal serum sodium is rendered more challenging in a humid subtropical environment, where insensible losses are higher. Abstract : Diabetes insipidus without perception of thirst, as may follow an anterior communicating artery aneurysm, requires prescription of fluid intake as well as desmopressin. The management goal of maintaining a normal serum sodium is rendered more challenging in a humid subtropical environment, where insensible losses are higher.